2016
DOI: 10.4172/2329-6836.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Semiemperical Investigation of the Postmenopausal Breast Cancer Treatment Potential of Xanthone Derivatives

Abstract: Aromatase, a catalyst in the aromatization reaction of androgens to estrogen, is a member of the cytochrome p450 superfamily, known as monooxygenases. The synthesized estrogen by Aromatase in breast cancer nourishes the cancer cells and assesses the hormonally growing of cancer cells. Therefore, Aromatase is considered as a potential target in treatment of breast cancer. Nowadays, major considerations in drug's selection in the treatment of cancers are shifted to natural sources due to their low toxicity profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…QP log S and # metab are used to predict the aqueous solubility and number of likely metabolic reactions. 44 The results indicated that all three compounds were in the recommended ranges of QPPCaco and # metab. In the case of CIQP log S, all three compounds were not found to be in the acceptable range.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…QP log S and # metab are used to predict the aqueous solubility and number of likely metabolic reactions. 44 The results indicated that all three compounds were in the recommended ranges of QPPCaco and # metab. In the case of CIQP log S, all three compounds were not found to be in the acceptable range.…”
Section: Resultsmentioning
confidence: 92%
“…One of the factors to predict intestinal absorption or permeation is the Caco-2 cell permeability (QPPCaco), which is used as a model for the gut–blood barrier. QP log S and # metab are used to predict the aqueous solubility and number of likely metabolic reactions . The results indicated that all three compounds were in the recommended ranges of QPPCaco and # metab.…”
Section: Resultsmentioning
confidence: 99%
“…MM‐GBSA is a popular method for predicting binding free energy. Scoring functions are used to predict the lowest energy poses, which determine the accuracy of docking results, and to predict the binding affinity of ligands toward the protein 24,25 . The top 10 docked ligands from the XP docking results were used to calculate MM‐GBSA free energy using the variable‐dielectric generalized born (VSGB) solvation model.…”
Section: Resultsmentioning
confidence: 99%
“…Log S, #metab and QPPCaco-2 are the parameters for prediction of aqueous solubility levels, the number of likely metabolic reactions and permeability of the gut–blood barrier (nm/s), respectively. 43 Qikprop employs a complex set of parameters for the prediction of bioavailability, including RO3, human oral absorption percentage, qualitative human oral absorption and the conformation-independent aqueous solubility (CIlog S), based on the similarity of compounds with their close analogs, which were practically tested. If the similarity of a designed compound and a respective known analog is < 0.9, the Qikprop prediction is used for logS and logP (permeability prediction).…”
Section: Resultsmentioning
confidence: 99%
“…P pred is predicted property, S is the similarity, and P exp and P QP are the respective experimental and QikProp predictions for the most similar molecule within the training set. logP is predicted based on the physiochemical properties such as size, flexibility depending on the NRB, 43 overall lipophilicity, shape and the capacity to make hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%